(untitled) (Nepalese Journal of Radiology, 2024)
Actinomycosis is caused by non-spore-forming, anaerobic, gram-positive bacteria called actinomyces. Its wide range of manifestations and non-specific symptoms cause complications by delaying diagnosis. We here present a case of a 34-year-old female with a history of recurrent discharging sinus and skin rashes in the posterior chest wall for 1 year and 6 months. Initially, it was suspected of malignancy with secondary infection. The patient was advised for MRI which shows suspicion of actinomyces. Later on, it was confirmed with a biopsy of the posterior chest wall. Here we present a case to describe the role of MRI in the diagnosis of actinomycosis.